Combined salivary duct carcinoma and squamous cell carcinoma suspected of carcinoma ex pleomorphic adenoma. Issue 8 (19th July 2016) - Enokida, Tomohiro; Fujii, Satoshi; Kuno, Hirofumi; Mukaigawa, Takashi; Tahara, Makoto; Sakuraba, Minoru; Hayashi, Ryuichi
Abstract : A 76‐year‐old Japanese woman had noticed an asymptomatic and palpable mass in her left parotid gland region for 20 years. The tumor had showed rapid growth during the last two months. Therefore, the tumor was clinically suspected of being a malignant tumor and was surgically resected. A histopathological examination revealed that the tumor consisted of two different histopathological neoplastic components accompanied by hyalinized fibrosis at the center of the tumor. The two‐neoplastic components were squamous cell carcinoma and salivary duct carcinoma. The tumor was suspected to be a carcinoma ex pleomorphic adenoma after considering the clinical course and the histopathological findings, such as hyalinized fibrosis at the center of the tumor. There was no evidence of recurrence at 30 months after the surgical resection.